Optimizing Decommissioning: Reuse of Fixed Steel Jacket - Othman, Amirul Ashraf (Universiti Teknologi PETRONAS, 2017)
Now, in Malaysia, offshore decommissioning just began its era due to Malaysia contain a lot of ageing offshore platform which mostly consist of fixed platform but from time to time decommissioning will be increase to a level where it will be known as a practice for removal of offshore platforms in Malaysia. Decommissioning has a few methods such as complete removal, partial removal, reefing or reusing of the offshore structure. Reusing plan is said that it can be the optimum ways in a better aspect in term of sustainability which the steel jacket has its strength even though the platform is ageing. The typical problem which held in the jacket is the joint but not the entire steel member. Thus, with reused plan can possibly be the optimum way in decommissioning. In this project, it will be focused on to do assessment on a few platforms and the analysis from the results. Therefore, this project is being carried out in order to know the feasibility of reused plan for offshore structure in Malaysia.